Validation of the Italian version of the pediatric CMT quality of life outcome measure. Issue 2 (3rd May 2022) - Moroni, Isabella; Danti, Federica Rachele; Pareyson, Davide; Pagliano, Emanuela; Piscosquito, Giuseppe; Foscan, Maria; Marchi, Alessia; Ardissone, Anna; Genitrini, Silvia; Wu, Tong Tong; Shy, Michael E; Ramchandren, Sindhu
Abstract: The pediatric Charcot‐Marie‐Tooth (CMT) specific quality of life (QOL) outcome measure (pCMT‐QOL) is a recently developed and validated patient‐reported measure of health QOL for children with CMT. The aim of this study was to provide and validate an Italian version of the pCMT‐QOL. The original English version was translated and adapted into Italian using standard procedures. pCMT‐QOL was administered to patients genetically diagnosed with CMT, aged 8 to 18 years. A retest was given 2 weeks later to assess reliability in all patients. A total of 22 patients (median age 14 years, DS 2.5; M:F 1:1) affected with CMT (19 CMT1A, 2 CMT2A, 1 CMT2K) were assessed as part of their clinical visit. The Italian‐pCMT‐QOL demonstrate a high test‐retest reliability. None of the patients experienced difficulty in completing the questionnaire, no further corrections were needed after administration in patients. The Italian‐pCMT‐QOL is a reliable, culturally adapted and comparable version of the original English pCMT‐QOL. This questionnaire is expected to be valuable in monitoring disease progression and useful for future clinical trials in Italian‐speaking children with CMT.